USING DIGITAL PLATFORMS TO ENHANCE STUDENTS’ SPEAKING SKILLS IN ESL CLASSROOMS - Ismailova Roziya Bahodir qizi (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract: This study investigates the effectiveness of using digital platforms to enhance students’ speaking skills in English as a Second Language (ESL) classrooms. The research explores how online tools such as Zoom, Flipgrid, Duolingo, and SpeakUp improve learners’ pronunciation, fluency, and confidence in oral communication. A mixed-method approach was applied, combining classroom observations, student surveys, and teacher interviews. Results indicate that integrating digital platforms provides learners with more opportunities for interaction, self-recording, and feedback, leading to improved speaking performance. Moreover, these platforms increase learner engagement and autonomy, offering flexible learning environments beyond traditional classroom boundaries. The findings suggest that digital tools can be used effectively as supplementary resources to develop students’ communicative competence. The study concludes that teachers should incorporate digital technologies systematically to make speaking lessons more interactive and motivating.